Optimal power flow using FACTS devices : soft computing techniques - Kumar, L. Ashok; Sundaram, K. Mohana (Boca Raton, FL : CRC Press, 2021)
Optimal Power Flow Using FACTS Devices: Soft Computing Techniques develops intelligent algorithms to analyze optimal power flow (OPF) and to enhance the power transfer capability of the transmission line with reduced congestion. By providing elaborate studies on FACTS devices and by using soft computing metaheuristics algorithms such as Firefly, Cuckoo, Flower Pollination, and others., this book enables readers to know about algorithms in real-time power system applications and damping of subsynchronous resonance (SSR) oscillations. Key features of this book include: Offers comprehensive review of FACTS devices and the importance of soft computing techniques for solving OPF. Describes the various problems associated with power system operation and control. Addresses issues of SSR in power systems and proposes soft techniques for SSR analysis in power systems. Demonstrates of the importance of SSR and congestion management using intelligent FACTS devices as part of OPF. Covers power systems' reliability, quality, cost-effectiveness, effects on customer goodwill, and pollution limits, including the deregulation of markets and different intelligent controllers. Optimal Power Flow Using FACTS Devices: Soft Computing Techniques is aimed at researchers and professionals in the field of power systems.
OCLC-licensed vendor bibliographic record.
Keywords: Flexible AC transmission systems; Electric power systems -- Control; Soft computing; MATHEMATICS / General; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General